The geology, sedimentology, geochronology and palaeo-environmental reconstruction of the Heelbo hillslope deposit, Free State Province, South Africa - Evans, Mary Yvonne (My University, 2016)
A multidisciplinary sedimentological, stratigraphic, mineralogical and geochronological analysis of a small, fossil-bearing, Holocene hillslope deposit, flanking a mesa, has enabled a reconstruction of the palaeo-environmental history of the region. The hillslope deposit, located on the farm Heelbo in the eastern Free State Povince, South Africa, overlies Jurassic mudrock and sandstone of the Elliot Formation, Karoo Supergroup. The deposit is located on a steep (~10°) slope and covers an area of ~7 km2 in two separate sections. It extends ~475 m downslope and reaches a maximum thickness of at least 6-8 m towards the base. Mineralogy indicates the deposit is sourced from the mesa but its fine grain size and location on a steep slope position Heelbo outside the scope of traditionally described alluvial fans or colluvial deposits. The hillslope deposit is described as an alluvial slope based on the morphology of the deposit and the grain size distribution against the slope gradient. The deposit comprises fine-sand to silt- grain size, but is found on a steep (~10°) slope. The source of the sediment is shown to be the sediment of the mesa, rather than input from an aeolian source. The grains are described as sub-angular and poorly sorted which also suggests a local provenance for the sediment. Microscopic and XRF analysis confirm the derivation of the sediment from the Elliot Formation, with the lithic fragments derived from subarkoses to arkoses of the underlying bedrock of the Upper Elliot Formation (UEF) in the Karoo Supergroup. Secondary calcite was visible in only two of the thin sections, thus it is likely due to a diagenetic overprint that is constrained by depth from the surface or time and not to specific layers. The deposit is cut by several mature and continuous gully networks with V-shaped profiles in the proximal slope, and combined V- and U-shaped profiles in the medial and distal sections. Gully formation is linked to both the sodium adsorption ratio (SARs), and high soil clay content, which facilitates swelling and shrinking. The Heelbo deposit comprises two palaeosols (BT1 and BT2) and four sediment (B1, B2, RB and TS) horizons. Through luminescence dating, the ages were found to be approximately 6390 ± 740 years BP for the oldest Brown (B1) horizon and 250 ± 170 years BP for the Red Brown (RB) horizon. The radiocarbon ages of the sediment were inconclusive, but the 14C ages of the fossil bones were in agreement with the luminescence ages. The multiple palaeosol horizons identified suggest two cycles of deposition, pedogenesis and erosion of the alluvial succession. The palaeosols and the presence of calcareous nodules and rhizocretions, and smectite and mixed-layer clay minerals, together with the total absence of illite and kaolinite, suggest protracted, dry periods with intermittent short periods of high rainfall. This is a similar climate regime to what the region experiences currently. Main findings: The Heelbo alluvial slope comprises locally derived sediment, rather than an aeolian source. Heelbo suggests that the hillslope deposits classification system needs to be re-evaluated and opens opportunities for wider study of Pleistocene-Holocene hillslope deposits in central / northern South Africa. This study also contributes to climate change debates in the Holocene.
Thesis submitted in fulfillment of the requirements for the Degree of Doctor of Philosophy University of the Witwatersrand South Africa 2015
Keywords: Sediments (Geology)--South Africa--Free State Province.; Geology, Stratigraphic--Holocene.; Climatic changes.